OFR-6(1)-81 Mine Electrical Power Systems - Transients Protection, Reliability Investigation, And Safety Testing Of Mine Electrical Power Systems - Vol. I - Transients In Mine Electrical Power Systems - E. K. Stanek (The National Institute for Occupational Safety and Health (NIOSH), 1979)
This report contains results of two major efforts related to electrical transients on mine electrical power systems. The first area concerns the use of digital computers to model mine electrical power systems and predict transients or duplicate field recordings of transients. Two existing general purpose circuit analysis programs were used. The first was the TRW Engineering System Simulator or TESS. The second was Electronic Circuit Analysis Program or ECAP. TESS proved to be superior to ECAP in several important characteristics, including system size limitations and modeling nonlinear elements. The second major topic covered in this report is the evaluation of commercially available surge suppression devices. These devices were found to be quite acceptable and guidelines for the selection and placement of surge suppressors were included. The final important item is a listing of the worst-case transients, from a design point of view, for ac and de utilization systems and ac distribution systems.